Wheat Response to Fertilizer Application Techniques and Nitrogen Levels: II. Crop Growth and Yield Attributes - Ullah, Ghazanfar; Khan, Ejaz Ahmed; Awan, Inayat Ullah; Khan, Muhammed Ayyaz; Khakwani, Abdul Aziz; Baloch, Muhammed Safdar; Khan, Qudrat Ullah; Jilani, Muhammad Saleem; Wasim, Kashif; Jilani, Ghulam; Mohib Ullah, Muhammad (Pakistan Journal of Nutrition, 2013)
Field experiment was conducted to evaluate difference among various levels of Nitrogen (N) fertilizer, its application techniques and their interaction on the growth, yield components and yield of wheat. Treatments of N fertilizer application techniques, viz., broadcast and side-dressing were allocated to main-plots and nitrogen levels, viz., 60, 90, 120, 150, 180 and 210 kg N/ha were placed in sub-plots. This experiment was repeated for two years with the same treatments. Results revealed that nitrogen application techniques had non-significant impact on most of the crop parameters except count of fertile tillers. Various rates of nitrogen showed significant influence on all the parameters under study and showed significantly higher grain yield of wheat with successive increase of dose up to 180 kg N/ha. Maximum plant height and biological yield were obtained under the highest nitrogen level, viz., 210 kg N/ha. However, the highest count of fertile tillers, spike length, number of grains, 1000-grain weight and harvest index were recorded in the treatment receiving 180 kg N/ha. Interactions between fertilizer application techniques and nitrogen levels were non-significant for all the crop parameters studied in this experiment on wheat.